1993
DOI: 10.1017/s0950268800057009
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and surveillance of visceral leishmaniasis in the Campania region of Italy. The value of zymodeme typing

Abstract: Although human visceral leishmaniasis (VL) is a notifiable disease in Italy, there is evidence that the actual number of cases is far higher than that notified. A programme for active surveillance of VL in the 14 Italian endemic regions was launched by the Istituto Superiore di Sanità. We report data collected during a 3-year period of active surveillance in Campania, a south Tyrrhenian region covering 4.5% of the Italian territory. Out of 120 clinically suspected cases referred to medical and diagnostic refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…These observations reveal the problems that can arise as a result of a deficiently passive surveillance systems in the control of leishmaniasis, similar to those reported by other investigators. 13,14 More than 16% of the total of the people examined were LST positive. The magnitude of this response is similar to that recorded by other investigators in the central and western endemic areas of ACL in Venezuela.…”
Section: Discussionmentioning
confidence: 99%
“…These observations reveal the problems that can arise as a result of a deficiently passive surveillance systems in the control of leishmaniasis, similar to those reported by other investigators. 13,14 More than 16% of the total of the people examined were LST positive. The magnitude of this response is similar to that recorded by other investigators in the central and western endemic areas of ACL in Venezuela.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of vector activity in the Mediterranean countries [12,13,27], more clinical cases of sandfly fever may be seen in future.…”
Section: Immunoglobulinsmentioning
confidence: 99%
“…In the early 1980s, TOS was isolated in Italy from Phlebotomus perniciosus [5]. Phlebotomus sandflies are active in some Mediterranean countries, as indicated by the presence of leishmaniasis which is also transmitted by these vectors [12,13]. Recent studies in endogenous populations and case reports of infection in tourists indicate that TOS is endemic in the Italian regions of Tuscany and Marche, and also in Algarve, Catalonia and Cyprus [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that approximately 47% of the Sicilian population live in areas at risk for leishmania infection, these areas consisting mainly of rural areas, small villages, or peripheral districts of towns where the vector sandXy species are more abundant [14][15][16]. An epidemiologic survey conducted in Sicily between 1987 and 1995 revealed that the annual incidence of VL in the general population was 6 cases per 1,000,000 residents [17].…”
Section: Introductionmentioning
confidence: 99%